Analytical methods for the detection of clenbuterol. (May 2009) - Parr, Maria K; Opfermann, Georg; Schänzer, Wilhelm
Clenbuterol is therapeutically used for the treatment of pulmonary diseases such as bronchial asthma or for tocolytic reasons. In cattle feeding as well as in sports it is illicitly misused due to its anabolic properties to promote muscle growth. Sample preparation procedures and analytical techniques used for the detection of clenbuterol are manifold and vary with the objectives of the investigation. Methods for its detection in biological specimens, drug preparations, the environment, food and feed products are reported. They are mainly based on immunochemical, chromatographic and mass spectrometric techniques, or on capillary electrophoresis. Sample preparation primarily includes liquid–liquid extraction and solid-phase extraction. Depending on the aim of the method clenbuterol can be determined in single- or multi-analyte methods. In biological and environmental samples concentrations are generally low due to the potency of the drug. Thus, highly sensitive procedures are required for expedient analyses.